Description of Smoking Behavior in Adolescents ages 15-18 Years - Arbian Humaidi; Ade Gustiawan; Adi Rizfal Efriadi; Alief Jordan; Dandi Surya (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Smoking is a problem that has not been solved until now. Smoking has spread to various groups, from children to the elderly, men and women. This smoking habit can harm adolescents directly or indirectly which has been proven to interfere with the growth and development of adolescents. Many factors are associated with smoking behavior in adolescents aged 15-18 years. These factors are discussed based on research articles and book references. Factors that influence the relationship include peer association, price, and lack of parental attention. Smoking can increase the risk of several diseases, such as cancer, pregnancy disorders, and hypertension. Smoking too often not only causes problems in the development and growth of adolescents.